Lipid Hormones at the Intersection of Metabolic Imbalances and Endocrine Disorders - Maria-Zinaida Dobre; Bogdana Virgolici; Ruxandra Cioarcă-Nedelcu (Current Issues in Molecular Biology, 2025)
Lipid hormone imbalances involving glucocorticoids, thyroid hormones (THs), and sex hormones have widespread metabolic consequences, contributing to the global increase in obesity and insulin resistance. This review examines the complex role of disrupted lipid hormone pathways in the development of metabolic disorders, particularly metabolic dysfunction-associated steatotic liver disease (MASLD). Endocrine disorders such as hypercortisolism, hypothyroidism, and polycystic ovary syndrome (PCOS) are closely linked to MASLD through shared metabolic pathways. Mechanisms include glucocorticoid-induced gluconeogenesis and lipolysis, impaired lipid clearance in hypothyroidism, and the hyperandrogenism-induced downregulation of hepatic low-density lipoprotein (LDL) receptors. PCOS-related factors—such as central obesity, adipocyte hypertrophy, low adiponectin levels, and genetic predisposition—further promote hepatic steatosis. Thyroid dysfunction may also impair the hepatic deiodination of T4, contributing to lipid accumulation and inflammation. Given the overlapping pathophysiology among endocrine, hepatic, and reproductive disorders, multidisciplinary collaboration is essential to optimize diagnosis, treatment, and long-term cardiometabolic outcomes.